PENGARUH METODE PEMBIASAAN UNTUK MENANAMKAN KARAKTER JUJUR PADA ANAK USIA DINI USIA 5-6 TAHUN - Mulianah, Baiq; Purwati, Duwi; Mahmud, Bonita; Harpina, Harpina (Ihya Ulum: Early Childhood Education Journal, 2024)
The character of honesty is an attitude that should be developed from an early age through consistent training and habituation to become a ingrained habit. The purpose of this study is to determine the influence of habituation methods on instilling honesty character in early childhood aged 5-6 years. This research used a quantitative approach with a quasi-experimental one-group pretest and posttest design. The sample size consisted of 20 students determined using purposive sampling method. Data collection was conducted using observation sheets with Likert scale. Data analysis was performed using paired sample t-test with the assistance of IBM SPSS 23. The hypothesis testing results indicate that there is a significant difference between the average pretest and posttest scores in the development of honesty behavior, including indicators such as telling the truth, admitting mistakes, not hiding information, showing honesty in games, and having responsibility. It can be concluded that habituation methods can develop honesty character in early childhood aged 5-6 years.